PENINGKATAN KINERJA TENAGA KEPENDIDIKAN MELALUI IMPLEMENTASI ABSENSI SIDIK JARI - Ahfas .; Cut Zahri Harun; Sakdiah Ibrahim (Jurnal Administrasi Pendidikan : Program Pascasarjana Unsyiah, 2018)
Performance is the result of employees. Performance has to do with ability and motivation. This study aims to determine the performance of school administration through the implementation of fingerprint attendance at SMK Negeri 3 Banda Aceh. To achieve this goal, this research uses qualitative approach with descriptive method. The data was collected through interviews, observations, and documentation. Research subjects are principal, head of administration and school administration staff. The results showed that: The performance of school administration staff at SMK Negeri 3 Banda Aceh is good and professional. The Effort to improving their professionalism are: (1) training and socialization; (2) learn independently. The effort of the principal to improve professional school administration staff that principal gives chance for them on training and socialization and also coaching, and supervising. The factors affect of performance and professionalism of school administration staff are: a) Motivation. b) Leadership. c) Infrastructure facilities. d) Working climate. The application of finger print has been good in discipline and through the implementation of this application, the performance of school administration staff developed with quantity, quality and productivity of work.Keywords: Performance of school administration staff, and Implementation of Fingerprint